Synthesis, Structure, Hirshfeld Surface Analysis, and Antibacterial Activity of [Ni(3-NH₂py)₄Cl₂] Complex (3-NH₂py = 3-aminopyridine) - Putri Dwi Lestari; Nani Farida; I Wayan Dasna (Jurnal Kimia Sains dan Aplikasi, 2025)
Complex [Ni(3-NH2py)4Cl2] was successfully synthesized through the reaction between NiCl2·6H2O with 3-NH2py ligand with a mole ratio of 1:4 using the hydrothermal method at 120°C for 4 hours. The complex was characterized using the melting point test, electrical conductivity, FT-IR, and SC-XRD. The complex compound decomposed at 215°C. Typical absorption bands of 3-NH2py ligand appeared in the FT-IR spectrum of the complex at wave numbers 3375, 3323, 1585, and 1303 cm-1, indicating the presence of -NHas, -NHs, C=N, and -C-NH2 functional groups. The complex compound is an ionic compound that crystallizes in a distorted octahedral structure with a triclinic crystal system and space group Pī (a = 7.6428(8) Å, b = 8.5384(8) Å, c = 9.8610(13) Å and a = 73.920(4)°, b = 70.149(3)°, g = 71.036(2)°). The R-factor value is 4.48%, which shows the refinements are very close to the original structure. Based on the Hirshfeld surface analysis, the intermolecular interaction of N-H···Cl occurs between the H atom of the amine group and the ligand Cl in another molecule. Antibacterial activity tests against S. aureus and E. coli using chloramphenicol as a positive control. The results showed the inhibition zone diameters for both bacteria were 6.90 mm, higher than that of their free ligand.